Implementation of Infection Handling Protocols as a Form of Protection for Nurses in Providing Health Services - Anastasia Novi Herawati; Carol Taufiqurohman; Rafael Jasmin Berliana; Rahma Diah Asmarani (Immortalis Journal of Interdisciplinary Studies, 2025)
Implementing infection control protocols is a crucial step in protecting nurses as the frontline workers in healthcare. Hospitals, as healthcare facilities, face a high risk of infection, making disciplined adherence to health protocols crucial. These protocols must be implemented in accordance with the Standard Operating Procedures (SOPs) in force at each institution, which serve as guidelines for safe and professional work practices. However, various challenges can hinder nurses' adherence to established protocols. Factors such as workload, facility availability, weak supervision, and an incompletely established work safety culture are all obstacles that require attention. Furthermore, leadership and communication within the team are crucial for the successful implementation of these protocols. Understanding the various aspects that influence adherence to infection control protocols is expected to create a safer work environment and improve the quality of healthcare services for both patients and healthcare workers. Proper infection control is not only a procedural obligation but also a moral responsibility to ensure shared safety.